Pengembangan Lembar Kerja Peserta Didik Materi Teorema Pythagoras Kelas VIII dengan Pendekatan Realistic Mathematics Education - Oktavia, Siwi Putri; Palupi, Evangelista Lus Windyana (MATHEdunesa, 2025)
Although Kurikulum Merdeka encourages active and project-based learning, many teachers have difficulty compiling appropriate student worksheet. To overcome the difficulties experienced by teachers, it is necessary to conduct research on the development of student worksheet to be used as a reference by teachers. This study aims to describe the development process and the results of the validity, practicality, and effectiveness of RME student worksheet for the Pythagorean theorem. This development research uses the research design of ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Student worksheet was developed based on iceberg activities designed at the design stage. The ‘situational’ level solves the problem of the square tangram context, the ‘model of’ level constructing a right triangle from several square pieces and identifying its area, the ‘model for’ level determining the length of the sides of a right triangle, and the ‘formal’ level formulating the concept and formula of the Pythagorean theorem. The Realistic Mathematics Education approach is crucial in learning as it presents problems closely related to students' lives, helping them understand faster. This aligns with the Kurikulum Merdeka;s goal of using student-based experiential learning.. Validation was carried out by three validators, then the student worksheet was tested on 30 students of class VIII of SMP Negeri 24 Surabaya. The data collected included learning implementation data, student responses, and pre-test post-test. The validation results show that the student worksheets reached the very valid criteria with a score of 4.4048. The practicality of student worksheet based on the results of the learning implementation data analysis reached the very practical criteria with an average percentage of 94.79% and student responses reached the practical criteria with a total average of 80.20%. The effectiveness based on the N-gain score of student learning outcomes reached moderate criteria with a score of 0.49. This student worksheet focuses on a fun and familiar learning process through paper crafting activities, with students responding positively to it. Thus, the RME student worksheet for the Pythagorean theorem is proven to be valid, practical, and effective.